2012
DOI: 10.1136/annrheumdis-2011-200780
|View full text |Cite
|
Sign up to set email alerts
|

Do worsening scleroderma capillaroscopic patterns predict future severe organ involvement? a pilot study

Abstract: This pilot study is the first demonstrating an association between baseline NVC patterns and future severe, peripheral vascular and lung involvement with stronger odds according to worsening scleroderma patterns. This may indicate a putative role of capillaroscopy as a biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
125
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(143 citation statements)
references
References 12 publications
11
125
0
7
Order By: Relevance
“…These observations confirm the results of a recent longitudinal study that reported a dynamic transition of microvascular damage through different capillaroscopy patterns in nearly 50% of SSc patients (Smith et al, 2012;Sulli et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These observations confirm the results of a recent longitudinal study that reported a dynamic transition of microvascular damage through different capillaroscopy patterns in nearly 50% of SSc patients (Smith et al, 2012;Sulli et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…In order to clarify with further aspects the reported associations between nailfold capillary abnormalities and clinical and/or laboratory features (Bredemeier et al, 2004;Caramaschi et al, 2007;Chen et al, 1984;Cutolo et al, 2004;Hofstee et al, 2009;Lovy et al, 1985;Smith et al, 2012;Sulli et al, 2012) it was decided to evaluate a large multinational group of patients with SSc such as the international multicenter cohort of the EULAR Scleroderma Trials And Research (EUSTAR) registry.…”
Section: Introductionmentioning
confidence: 99%
“…We considered an organ system to be involved if the corresponding disease severity score was Ն1 (16). Severe organ involvement was defined as a disease severity score of Ն2 (17). Lung involvement was assessed by high-resolution computed tomography (HRCT) and pulmonary function testing.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the decreased number of capillaries is associated with clinical subsets and the severity of SSc clinical complications 2,3,4,5 .…”
Section: To the Editormentioning
confidence: 99%